Experiences with and attitudes toward interprofessional health care teams among American clinical, counseling, and school psychology doctoral students: a mixed methods study. Issue 2 (4th March 2021) - Patterson, Shannon L.; Caskie, Grace I. L.; Bashian, Hannah M.
ABSTRACT: Attitudes toward interprofessional collaboration influence interprofessional health care team (IPHCT) functioning and quality of patient care. Yet, research has not examined the attitudes and experiences of psychology doctoral students on IPHCTs. Utilizing a volunteer sample of 214 clinical, counseling, and school psychology doctoral students from at least 47 doctoral programs in the United States, this study aimed to clarify psychology doctoral students' experiences on IPHCTs and explore predictors of their attitudes toward IPHCTs. Discovery-oriented analysis and hierarchical multiple regression were used to identify themes of students' self-reported interprofessional experiences and significant predictors of positive attitudes obtained via online survey questionnaires. Students who had worked on IPHCTs commonly reported taking roles of mental health therapeutic service provision and consultation and reported difficulty with team dynamics and navigating hierarchical structures. Students perceived the psychologist role primarily as clinical expert and team leader. Students reported making positive contributions, increased competency in interprofessional practice, and improvement in patient care as the most common benefits of IPHCTs. Each additional year spent on an IPHCT was related to more positive perceptions of the quality of care delivered by IPHCTs as well as greater endorsement of positive interprofessional socialization practices.